Academia no terreiro ou terreiro na academia? a função da Faculdade de Teologia Umbandista no diálogo entre adeptos de religiões afro-brasileiras e acadêmicos na esfera pública - Carneiro, João Luiz de Almeida (2014)
The main purpose of this work is to understand the social position that Faculdade de Teologia Umbandista, that is, FTU (Umbandist Theology College) occupies in the milieu of specific discourses reverberating in the social sphere. The hypothesis here presented is that FTU fosters a new way of theological thinking that promotes dialogue between Afro-Brazilian religious and laic persons, especially the ones that hold position in the academic milieu, by means of the legal and traditional tenets socially established. The methodology used in this research consisted of bibliography review, contemplating reading, analysis and interpretations of books, periodicals, and audiovisual materials. On account of such methodology, a discussion of four central issues has been raised by which it is possible to verify the hypothesis of the thesis: public sphere, Afro- Brazilian religions, orality and written tradition, and FTU. Therefore, in order to introduce the resulting interactions, that is, the bridges between knowledge and practices, emphasis has been given to two different and very important kind of events: 21st Century Umbanda Congresses and two of 24 rites for worshipping Eshu